Coyuntura Económica - Avelino Martínez Sandoval; Guillermo Aponte; Holmes Sánchez Rengifo; Lilian Andrea Carrillo-Rodríguez; Martha Vázquez Olave; Leidy Ángel Giraldo (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2007)
Coyuntura económica